The Impact of Word Wall on Student Perception of Speaking Skill Improvement - Rowi harnoman (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
This research aims to improve the speaking skills of English Language Education students through the use of a Word Wall. Word Wall is a learning media that contains a collection of important words on a particular topic, which are displayed on the classroom wall. This research uses a qualitative approach with a classroom action research design. The research subjects were tenth-grade Malang MA students. Data was collected through questionnaires and speaking ability tests. The research results show that the use of Word Wall can improve students' speaking skills. Students become more active, confident, and fluent in speaking English. Word Wall helps students enrich their vocabulary, understand grammar, and organize their ideas well when speaking. Apart from that, the Word Wall also creates a more interesting classroom atmosphere and motivates students to be actively involved in learning. Keywords: speaking ability, Word Wall, English education.